Estrés académico en la formación online durante la pandemia del COVID-19 en estudiantes de la Facultad Jurídica Social y Administrativa - Atocha Requenes, Ventura Isabel (2022)
In Ecuador, the prevalence of university academic stress has been increasing and currently constitutes 83%. The purpose of the study was to identify the sources of academic stress, evaluate online satisfaction and know the relationship between both variables according to sex and age in students of the Legal, Social and Administrative Faculty of the National University of Loja in the academic period May-September 2020. The study had a quantitative, descriptive, cross-sectional cohort approach, with a probabilistic sample of 186 participants from 20 to 31 years of age; The Academic Stress Inventory (IEA) and the University Student Satisfaction Questionnaire towards online training (CUSAUF) were applied. Obtaining that the two main sources of stress in both sexes and age groups were academic overload (X̅=4.09) and lack of time to complete academic activities (X̅=3.86). In online training, the aspect with the greatest satisfaction in both men and women aged 20 to 31 was that related to the platform or virtual environment (X̅=2.75). However, the aspects with the least satisfaction were for men of both groups (20-25 years old X̅=2.66 and 26-31 years old X̅=2.57) and women 26-31 years old (X̅=2.58) those related to the contents of the course; in the female group 20-25 years of age, those related to communication (X̅=2.86) and in the male gender, those related to the subject (X̅=2.66). Concluding that the female sex from 20 to 25 years old presented a statistically significant relationship between the variables